Kajian Theologis Dalam Mengetahui Tanda-Tanda Zaman Serta Respon Orang Percaya Dalam Mengatasinya - Olohesi Warae; Aprianus Lendrik Moimau (Jurnal Silih Asah, 2024)
This article examines the theological aspects and practical responses in facing the signs of the end times in the context of Christianity. Through analysis of theological views on the signs of the end times and the responses of Christian believers, this article discusses the importance of Biblical understanding, increasing faith, and concrete action in responding to the challenges of the end times. The role of church leaders in guiding the congregation and the need for interfaith dialogue were also debated. In conclusion, this article emphasizes the importance of striking a balance between solid theological understanding and relevant practical responses in the face of an uncertain future. it explores the concept of signs of the times in Christian theology. Based on Biblical teachings, these signs are interpreted as part of God's plan of salvation and foreshadowing the end times that will be concluded with the return of Christ. This understanding of the signs of the times influences the beliefs of Christian believers and raises questions about how they should respond to them.responses of Christian believers to the signs of the times. This response includes increased faith, hope, and spiritual readiness. Believers may increase their obedience to the teachings of the Bible, deepen their personal relationship with God through prayer and meditation, and strive to live according to the values ​​of the gospel in all aspects of life.